ASSESSING TOURISM STUDENTS’ ENGLISH PROFICIENCY COMPETENCE BASED ON ASEAN COMMON COMPETENCY STANDARD - Ni Nyoman Yunike Kurniarini; Untung Waluyo; Kamaludin Yusra (Yavana Bhasha : Journal of English Language Education, 2021)
This study is aimed to analyze the tourism students’ English proficiency competence basedon ASEAN Common Competency Standard (ACCS). The study used a descriptive qualitativemethod and the data were gained through English competency based workplace assessment for thestudents in three sub divisions at PDD Lombok Barat; hotel accommodation, culinary, and hotelengineering. The findings of the study showed that more than half of tourism students are still in thecategory of “low competence” in attaining English competencies based on ACCS.